Law Enforcement Regarding the Grounds of Bad Faith in Trademark Cancellation Lawsuits - Ria Harapenta Tarigan; Saidin Saidin; Putri Rumondang Siagian (Journal of Progressive Law and Legal Studies, 2026)
The exclusivity of a trademark as a distinguishing sign for goods and/or services must be registered. An application for trademark registration must be submitted by an applicant acting in good faith. A trademark registration may be cancelled by the Commercial Court within a period of 5 (five) years after the trademark has been registered, and there is no time limitation if it is proven that the trademark registration was filed in bad faith. This study aims to analyze the legal regulation of good faith in trademark registration, examine the concepts and criteria of bad faith in trademark cancellation practices, and analyze judges’ legal considerations in deciding trademark cancellation cases involving bad faith. This research is descriptive-analytical in nature and employs statutory, conceptual, and case approaches supported by secondary data. The data were analyzed qualitatively. The results of the study indicate that the concepts and criteria of bad faith are not clearly regulated in Law Number 20 of 2016 concerning Trademarks and Geographical Indications, resulting in inconsistencies in legal certainty and law enforcement. The contribution of this research is to provide a deeper understanding of the importance of clearer regulations regarding indicators of bad faith as a basis for legal protection for rightful trademark owners, as well as to serve as a consideration for lawmakers in improving trademark regulations in Indonesia. Therefore, it is recommended that provisions regarding the good faith of trademark applicants be regulated more clearly, specifically, and comprehensively.